Evaluating the Structural Model of IPAS Learning in Elementary Education: A PLS-SEM Approach to Influence Attention, Invested Learning, and Perceived Behavioral Control - Anastassia Ayunandita; Nayla Fadila; Gina Tantriyana Putri (CV. Akademi Merdeka, 2025)
This study aims to empirically test the relationship between attention, invested learning in acquiring skills and knowledge, control perceived behavior, and​ results Study in context basic education. The method used in this study is Partial Least Structural Equation Modeling (PLS-SEM), which allows analysis complex relationships between variables. Data were obtained from 240 elementary school students in Cirebon City through questionnaire scale Likert. The results of the analysis show that attention has significant influence​ to control behavior (β = 0.274; t = 4.763; p = 0.000) and learning engagement also showed a significant influence (β = 0.154; t = 2.256; p = 0.024). The R² value of 0.103 identified that the model was only able to explains 10.3% of the variance in control perceived behavior, which means that Still There is other variables outside the model that affect the dependent variable. The research findings indicate that the attention given to students, the learning invested , and control perceived behavior​ own significant influence​ and positive on learning outcomes. The practical implications of these findings encourage learning development strategies that focus on optimizing student attention and participation to improve learning effectiveness at the elementary education level.